Fear of Crime: Definition, Measurement, and Predictors - Işıl ÇOKLAR; Nevin SOLAK (Nesne Psikoloji Dergisi, 2017)
Fear of crime is a complex and multifaceted phenomenon consisting of cognitive, affective, and behavioral dimensions. This concept is defined as a negative emotional reaction of dread or anxiety to crime or the symbols associated with crime (Ferraro & LaGrange, 1987). In recent years, fear of crime has been recognized as an important social problem. Conceptualizing, measuring, and analyzing this concept, therefore, have received increased attention in interdisciplinary research. Research on fear of crime has addressed four specific theoretical approaches, namely the vulnerability, victimization, disorder, and social integration models. The aim of the current work was to examine the existing literature on fear of crime and make some suggestions for further research. First, we provided a short review of the definition, measurement, and determinants of fear of crime. Next, we made some suggestions for future research.